Kym Anderson y Vicente Pinilla (eds.). Wine Globalization. A new Comparative History. Cambridge, Cambridge University Press., 2018, 546 pp. ISBN: 978-1107192928. - Medina-Albadalejo, Franciso J. (Investigaciones de Historia Económica, 2020)
Sin resumen